Labor Market and Institutional Drivers of Youth Irregular Migration: Evidence from the MENA Region - Ghassan Dibeh; Ali Fakih; Walid Marrouch (Institute of Labor Economics (IZA), 2018)
Irregular migration became an alarming issue over the last decade for both developed and developing countries. A prevailing assumption in migration policy is that labor market and institutional characteristics play a crucial role in pushing people to leave their home countries in search for better life prospects. This paper examines this hypothesis using a unique dataset covering young people aged 15 to 29 from five major MENA countries from the year 2016. Using a probit model, the paper finds that labor market drivers (unemployment, job sector, social security, contract type) are of great importance for the decision to migrate irregularly amongst the youth in the MENA region and that the quality of institutions matters. In addition, the lack of wealth and economic opportunities enhance their willingness to engage in irregular migration.
Keywords: J61; O17; 330; irregular migration; youth; labor markets; institutions; Arab Spring